1996
DOI: 10.2307/1543012
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Mobilization During Germination of Post-Diapausing Gemmules of the Freshwater Sponge Eunapius fragilis

Abstract: Post-diapausing gemmules of the freshwater sponge Eunapius fragilis were found to contain sorbitol and glycogen as their primary carbohydrates. The sorbitol probably acts to increase the tolerance of the gemmules to freezing and desiccation. During germination, average sorbitol levels--measured as micromoles of sorbitol per gram of fresh weight of gemmule tissue (μmol/gfw)--declined from a control value of 36 μmol/gfw to about 4 μmol/gfw. Concomitantly, average glycogen levels increased from a control value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Organic particles, microalgae, and marine microorganism are food for field-growing sponges. Sorbitol was primary carbon source for the sponge Eunapius fragilis in the diapause period to protect it from cold and dry conditions (27). Pyruvic acid was also considered as a useful carbon source for the sponge S. domuncula (4).…”
Section: Resultsmentioning
confidence: 99%
“…Organic particles, microalgae, and marine microorganism are food for field-growing sponges. Sorbitol was primary carbon source for the sponge Eunapius fragilis in the diapause period to protect it from cold and dry conditions (27). Pyruvic acid was also considered as a useful carbon source for the sponge S. domuncula (4).…”
Section: Resultsmentioning
confidence: 99%
“…The osmolytes responsible for these observations and the effects they have on cell division and respiration have not, as yet, been examined. In a previous article (Loomis et al 1996), we showed that sorbitol was present in the cells of quiescent Eunapius fragiUs gemmules and that the concentration of sorbitol decreased dramatically during the early stages of germination. Further, we showed that the reduction of sorbitol is due to an increase in the activity of sorbitol dehydrogenase and that the sorbitol is most likely being converted to glycogen.…”
Section: Introductionmentioning
confidence: 85%
“…Diapause and quiescence are characterized by a greatly reduced metabolic rate, as demonstrated by low rates of oxygen consumption and metabolic heat production. Both heat dissipation and oxygen consumption rates were very low in diapausing and quiescent gemmules of £ fragiiis (Loomis et al 1996), and these rates increased steadily during germination, reaching 600% of the starting level by the time ceils emerged from the gemmule. To test the hypothesis that increased osmotic concentration maintains the gemmules in quiescence, we measured the effects of increased osmotic concentration on the rate of oxygen consumption in both E. fragiiis and A. ryderi.…”
Section: Effects Of Osmotic Goncentration On Oxygen Gonsumpttonmentioning
confidence: 95%
See 2 more Smart Citations